Even more in the pandemic and social emergency: for an individual welfare beyond the family and the community. Issue 2 (15th March 2022) - Cataldi, Laura; Tomatis, Francesca; Costa, Giuliana
ABSTRACT: In many welfare regimes, families and communities are often considered as social policy solutions to the extent that they are called into action to provide support and care services. The resort to 'family' and 'community' seems to contrast the atomization of today's society, but it entails two risks: first, the privatization of welfare; second, the exclusion of the most fragile and needy people, as well as individuals without a network. The COVID-19 pandemics have made these risks even more evident: the crisis has exacerbated the centrality of informal networks in producing welfare services and helps. These are the reasons why it is necessary to reflect on the need to primarily develop an individual – rather than a family and community – welfare.